The Palgrave Handbook of Gender and Healthcare
XXI, 482 p.
Keywords: An authoritative, state-of-the-art reference collection, bringing together international experts to examine the key issues and core debates related to gender and healthcare. A vital resource for a wide range of academics, researchers, practitioners and policymakers.